'No one remains living in the past': the dynamics of pottery technological styles in southwestern Ethiopia. Issue 1 (2nd January 2021) - Wayessa, Bula
ABSTRACT: This article examines the pottery technological styles of the Oromo, the Yem and the Dawro ethnolinguistic groups in southwestern Ethiopia. It provides a comparative examination of the technological choices each group makes at different stages of pottery production, which, in turn, produce and reproduce their group identities. In southwestern Ethiopia, pottery-making lies within the domain of women, with social restrictions prohibiting male involvement. Potters are marginalised and transmit pottery-making knowledge and skills through learning networks, mainly between immediate family members. Each pottery-making community practises distinct technological traditions and styles, but all communities are now acquiring new technological skills in response to developing socio-economic dynamics. Examination of the incorporation of new elements into pottery-making due to both socio-economic changes at the local level and global phenomena may provide clues about the changing dynamics of the craft in the recent and more distant past.